ASSESSMENT OF SOIL CONTAMINATION CAUSED BY UNMANNED AERIAL VEHICLE FALLS AS AN OBJECT OF ENVIRONMENTAL INSPECTION (CASE STUDY OF KRASNOSILKA VILLAGE, STAROKOSTIANTYNIV URBAN TERRITORIAL COMMUNITY) - SHEVCHENKO, SERGII; YEFREMOVA, OLHA; SHEVCHUK, NATALIIA; STOPNYK, ROMAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents a comprehensive eco-geochemical evaluation of soil contamination resulting from the fall and detonation of Unmanned Aerial Vehicles (UAVs) in Krasnosilka village, Starokostiantyniv urban territorial community. Intensive military activity has led to the formation of localized pollution zones containing residues of fuels, lubricants, explosive compounds, composite materials and metal fragments. Field sampling and laboratory analysis revealed elevated concentrations of heavy metals – particularly lead, cadmium, chromium, arsenic, mercury and iron – compared to background levels, with several toxicants exceeding Maximum Permissible Concentrations. These findings confirm the emergence of highly contaminated micro-sites that pose risks to agroecosystems through reduced soil fertility, impaired biological activity and potential bioaccumulation of pollutants in agricultural products. The study highlights the need for systematic environmental inspection, including spatially differentiated sampling, assessment of biological toxicity, and continuous monitoring of contaminant migration. Based on the obtained results, the paper proposes an integrated set of environmental mitigation and restoration measures. Priority is given to cost-effective biological remediation strategies, such as phytoremediation using metal-accumulating crops and the application of microbial biotechnologies to restore soil microbiota. For critically damaged areas, temporary land conservation is recommended to prevent further ecological degradation. The research provides scientifically grounded recommendations for improving environmental inspection procedures and establishing an effective system for post-war soil rehabilitation in agricultural landscapes.
Keywords: soil contamination; unmanned aerial vehicles (UAVs); heavy metals; environmental inspection; environmental monitoring; phytoremediation; agroecosystems; recultivation / reclamation; phytomelioration